Sustainable Work Engagement: The Role of Work-Life Balance, Organizational Support, and Mental Well-Being (A Systematic Review) - Nugroho, Johanes Aji; Riyanto, Setyo; Suprapto, Suprapto; Herminingsih, Anik (Journal of Management and Business Review, 2026)
This study aims to synthesize empirical evidence on how Work–Life Balance (WLB) and Perceived Organizational Support (POS) sustain work engagement through mental well-being as a mediating mechanism. Following PRISMA 2020, a Boolean search across Scopus yielded 1,339 records; after systematic screening, 165 peer-reviewed articles (2020–2026) were included. Analysis reveals three key findings: (1) mental well-being is predominantly operationalized through deficit indicators (burnout, stress) rather than positive capacities (resilience, flourishing); (2) cross-sectional designs dominate, undermining temporal validity of "sustainability" claims; and (3) the JD-R framework prevails, yet cross-theoretical integration with COR and SET remains largely narrative. The novelty of this research lies in the integration of mental well-being typologies and methodological design patterns into a single explanatory synthesis regarding sustainable work engagement. These findings provide a foundation for evidence-based HRM interventions, longitudinal monitoring strategies, and policy alignment with SDGs 3 and 8, advancing understanding of work engagement as an organizational ecosystem phenomenon rather than a singular outcome.